In their own words: developing the Parent Experiences Questionnaire following neonatal brain injury using participatory design. (19th September 2018) - Williams, Tricia S; McDonald, Kyla P; Roberts, Samantha D; Westmacott, Robyn; Ahola Kohut, Sara; Dlamini, Nomazulu; Miller, Steven P
ABSTRACT: Primary objective : This study aimed to create a specific questionnaire (Parent Experiences Questionnaire) about early experiences, service involvement, and needs of children and parents following neonatal brain injury that could be used to inform clinical care and needed interventions. Research design and methods : A mixed-method design was utilized, engaging in both qualitative and quantitative methods across three phases. Phase 1 employed participatory design involving 12 parent and clinician participants in semi-structured interviews to address main topics, item importance, and overall impressions of the questionnaire. In phase 2, the questionnaire was piloted by 32 parents. Post hoc revisions added four questions to address current parent and child therapeutic needs in phase 3. Main outcomes and results : The final questionnaire yielded 24 items addressing topics of early communication between parent and clinicians, early intervention services, efficacy, and barriers in optimizing the child's development and parents' experience. The questionnaire was reviewed positively by a group of parents in phase 2 and demonstrated good acceptance, online feasibility, stability, and association with current parental mental health and child development. Conclusions : This investigation offers a valuable new questionnaire to inform clinical care regarding discussions with parents about neonatal brain injury, evaluate the perceived efficacy of early intervention services, and guide relevant future intervention efforts.